PROCESSING OF EXHAUST LEADEN-CADMIUM GALVANIC ELEMENTS REPORT 2. FLOWSHEET OF PROCESSING - Дмитриков, В. П.; Падалка, В. В.; Проценко, О. В.; Коломєєц, В. І. (Scientific Progress & Innovations, 2013)
The results of researches on the reagent processing of exhaust leaden-cadmium galvanic elements and accumulators which serve as the second raw material for electrical engineering industry are produced. The features of the technological planning, ecological and economic aspects of processing, are considered. The stages of the processing of exhaust leaden-cadmium galvanic elements and accumulators are analyzed. The improved methodology is offered and the flowsheet of processing is developed.